Impact of insurance payer type (medicare vs. private) on the patient reported outcomes after shoulder arthroplasty - Paul V. Romeo, MD; Aidan G. Papalia, MBA; Andrew J. Cecora, BS; Bradley A. Lezak, MD; Matthew G. Alben, DO; Dashaun A. Ragland, BS; Young W. Kwon, MD, PhD; Mandeep S. Virk, MD (JSES International)
Background: This study’s purpose is to determine if there is a difference in patient-reported outcome measures (PROMs) following shoulder arthroplasty (SA) based upon payer insurance type, with a secondary outcome of determining if any appreciable difference surpasses the minimal clinically important difference (MCID). Methods: Subjects undergoing anatomic and reverse total shoulder arthroplasty were prospectively enrolled between March 2019 and March 2021. Subjects completed patient reported outcomes measurement information system upper extremity (P-UE), the American Shoulder and Elbow Surgeons score (ASES), and the simple shoulder test (SST) preoperatively and at 2 weeks, 6 weeks, 3 months, 6 months, and 12 months, postoperatively. Descriptive statistics of baseline patient characteristics and preoperative PROMs (ASES, SST, and P-UE) were compared between insurance types. Results: 143 patients were identified who met the inclusion criteria for this study. There were 98 patients within the Medicare cohort and 45 patients with private insurance. Patients in the Medicare cohort were older (mean age 70.5 vs. 61.3 years), with high proportion of smokers, diabetics, and reverse total shoulder arthroplasty compared to the private payor cohort. There were no significant differences between the two cohorts with respect to outcomes scores except for significantly better SST in the private insurance cohort (69.3 vs. 79.4, P = .02). No significant differences were noted for the achievement of MCID between cohorts [P-UE (P = 1.0), ASES (P = .25), and SST (0.52)] and pre-to-postoperative improvements for P-UE (P = .62), ASES (P = .4), or SST (0.66). Conclusion: Our study demonstrates that, at a tertiary-level academic institution in a metropolitan city, payor type does not have significant impact on achieving MCID or pre-to-postoperative improvements in PROMs after SA.